On the usability of synthetic measures of mutual fund net-flows - Silke Ber; Stefan Ruenzi (University of Cologne, Centre for Financial Research (CFR), 2006)
Due to a lack of data availability, numerous empirical studies on mutual fund flows (e.g. Sirri/Tufano (1998)) analyze synthetically derived flow measures. We show how good these measures can explain actual flows. We compare the measures suggested in the literature with the actual net-flows of all German equity mutual funds. Our results show the appropriateness of the synthetic measures used in previous studies. Inference about the influence of past performance on flows is not biased by using synthetic instead of actual measures of fund flows. Thus, we offer a justification for the use of synthetic measures in performance flow studies.
Keywords: G23; G20; G29; G24; 330; Mutual Funds; Performance Flow Relationship; Synthetic Flow Measures; Net-Flows